2016
DOI: 10.1016/j.ecoser.2015.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Does nature conservation enhance ecosystem services delivery?

Abstract: Whilst a number of studies have examined the effects of biodiversity conservation on the delivery of ecosystem services, they are often limited in the scope of the ecosystem services (ES) assessed and can suffer from confounding spatial issues. This paper examines the impacts of nature conservation on the delivery of a full suite of ES across nine case studies in the UK, using expert opinion. The case studies covered a range of habitats and explore the delivery of ES from a 'protected site' and a comparable 'n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 37 publications
3
48
0
2
Order By: Relevance
“…Thus, PAs appear to be set to continue to deliver high biodiversity benefits, even if the relative abundances and identities of the species present changes. Regulatory ecosystem services provided by PAs may also continue to operate despite a changing biota (Eastwood et al ., ). Empirical evidence, however, remains sparse.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, PAs appear to be set to continue to deliver high biodiversity benefits, even if the relative abundances and identities of the species present changes. Regulatory ecosystem services provided by PAs may also continue to operate despite a changing biota (Eastwood et al ., ). Empirical evidence, however, remains sparse.…”
Section: Discussionmentioning
confidence: 97%
“…(2017) demonstrated that only half of the areas in the Columbian Andes, where biodiversity and ecosystem service supply is high, lay within protected zones. Eastwood et al () conducted a paired approach at the landscape scale on protected and unprotected areas in Britain and concluded that protected areas provide higher levels of cultural and regulating ecosystem services. Similarly, Castro et al () found that protected areas in arid landscapes in Spain supplied marginally higher levels of regulating services.…”
Section: Introductionmentioning
confidence: 88%
“…Conversely, ecosystem services, such as clean water or erosion control, have been rarely used in conservation planning, apart from justifying biodiversity conservation needs (Balvanera et al ., ; Egoh et al ., ). Even the ecosystem services have been only used as justification in conservation planning, recent studies have shown that ecosystem services are more found in protected areas when compared to non‐protected areas (Castro et al ., ; Eastwood et al ., ). Still, it is unclear the extent to which biodiversity could function as a surrogate for ecosystem services when defining protected areas.…”
Section: Introductionmentioning
confidence: 99%